Die erinnerte Revolution / Mémoire(s) de la Révolution Tagungsakten der Sektion 5 des XI. Kongresses des deutschen Frankoromanistenverbandes "Krieg und Frieden. Zur Produktivität von Krisen und Konflikten" / Actes de conférence de la section 5 du XIe congrès de l'Association des francoromanistes allemands "Guerre et paix. Crises et conflits - nouvelles perspectives" - Wörsdörfer, Anna; von Hagen, Kirsten (Romanische Studien Beihefte, 2021)
The French Revolution represents the defining event in modern French national memory. As an epochal turning point with profound political and social upheavals, it presents itself - beyond the legislative implementations of an intellectual elite - in its concrete manifestations on the streets and public squares of Paris and in the provinces as a decisive episode in the modern history of France determined by aggressive physical conflicts. With the year of crisis that lasted from spring 1793 to summer 1794, the revolutionary events, after having evoked conflict with foreign powers since their beginnings, entered a new phase of (civil) war within the country, insofar as the Grande Terreur raised the internal French camp struggles with countless guillotine executions to a new level of escalation. The violent excesses that had become commonplace left traces in France's collective memory. On the one hand, such traces are still concretized in the revolutionary period itself. On the other hand, the French Revolution represents a privileged point of reference, especially in renewed times of crisis. The 19th century, with the subsequent revolutions of 1830 and 1848, the 20th century, with the two world wars, and the 21st century, with the most recent challenge of global terror, are not lacking in such phases of social destabilization and threatening political chaos. The present volume is dedicated to this revolutionary coming to terms with the past, especially the bloody phase of 1793/94, in its diverse manifestations from the late 18th century to the present.